Effect of Transcranial Direct-Current Stimulation and Task-Oriented Training on Electroencephalography-Based Motor Recovery Chronic Stroke: A Randomized Clinical Trial - Maryam Zolghadr; Shohreh Noorizadeh Dehkordi; Javad Sarrafzadeh; Saeed Talebian; Hassan Haddadzade Niri; Marzieh Yassin (Journal of Modern Rehabilitation)
Introduction: Upper limb motor disability, with a prevalence of approximately 77%, is the most common complication after stroke. Despite advancements in rehabilitation, many patients face persistent upper limb discrepancies. Adopting top-down and bottom-up interventions may enhance neuroplasticity and improve upper limb function. This study aims to determine the effect of motor cortical transcranial direct-current stimulation (tDCS) as a top-down approach combined with task-oriented training (TOT) as a bottom-up intervention on changes in electroencephalography (EEG) spectral power in chronic stroke patients. Materials and Methods: Thirty chronic hemiparetic stroke survivors were randomly assigned to receive real or sham stimulation targeting the primary motor cortex (C3/C4) at 2 mA for 20 minutes and TOT daily over 15 sessions. EEG was conducted before and after the intervention, with a 3-month follow-up and the relative powers of delta to gamma frequency bands were recorded during the movement task with each hand (healthy and involved). Results: Significant differences in the theta (P=0.000), alpha (P=0.004), beta (P=0.000) and gamma (P=0.003) relative powers were observed between groups at follow-up. Additionally, the Friedman test revealed a significant decrease in alpha and beta bands’ relative powers in the healthy hand of the control group at follow-up (P=0.001). The experimental group displayed increased alpha and beta powers and decreased theta without statistical significance. Conclusion: The increase in the relative power of low frequencies and the decrease in high frequencies in the sham group, which were more prominent than the increases in alpha and beta bands’ relative power and the decrease in theta in the experimental group, can indicate that the real-tDCS can prevent the recovery drop of relative powers. Due to the inconsistent effects of tDCS on the EEG power spectrum in stroke patients, conventional tDCS administration may require adjustments for optimal application to brain target points.